Upaya peningkatan hasil belajar peserta didik melalui model pembelajaran Probing-Prompting pada materi sistem gerak kelas XI IPA - Heliyana Zuriyati (CAHAYA PENDIDIKAN, 2022)
ABSTRACT The research activities carried out have the aim of obtaining information about how the effect of the application or use of the Probing-Prompting learning model on the learning outcomes of students in class XI IPA SMA Negeri 1 Tanjung Raja. The research that was conducted was using the Pre-Experimental Design method with the Random Sampling technique. The data obtained was carried out in class XI IPA 2 while the number of students was 31 people. The research instrument or tool used in the study is the initial and final test instrument in the form of multiple choice questions. The value obtained in the form of posttest average student learning outcomes, which is higher than the average value obtained during the pretest, which is 79.55 and 429.21. From the results of data analysis, hypothesis testing using t-test with the help of the Statiscal Program for Social Science. (SPSS20) the t-count is 38.358, while the t-table is 2.1423. From the results obtained, it can be concluded that tcount ttable, which is 38.3758 2.1423, which means H0 is rejected while Ha is accepted, so it can be concluded that the application of the Probing-Prompting learning model has a significant effect on student learning outcomes in class XI IPA SMA Negeri 1 Tanjung Raja on Motion System Material.Keywords: Probing-Prompting, Learning Outcomes, Movement System.